Melting expedition in horizontal triplex tube heat exchangers via radial and combined radial-axial fins. (10th December 2022) - Moradian, Ali; Ameri, Mohammad; Majidi, Sahand
Abstract: The effects of using radial fins on the melting of a Phase-Change Material (PCM) inside a horizontal Triplex Tube Heat Exchanger (TTHX) are investigated in this study. To this aim, several configurations of radial fins and their combination with conventional axial fins are considered. First, the melting in a TTHX equipped with axial fins is simulated to assess the validity of the solver. The numerical predictions agree well with the experimental data. Next, the melting process in a TTHX equipped with different configurations of radial fins is simulated to compare their thermal performance with that of the longitudinal fins. Effects of multiple parameters are investigated, such as the fin radii and number, replacing full circle fins with arc fins, and axial distribution of the fins. The results indicate that inserting arc fins in the lower section of the PCM enclosure improves the thermal performance significantly. This leads to an 18 % reduction in melting time when their axial spacing is non-uniform. Also, combined radial-axial configurations, considered in the present research for the first time, greatly accelerate the melting if the axial fins are located on the inlet side of the PCM enclosure and the radial fins are located on the other half. Highlights: Studying the melting of PCM in triplex-tube heat exchangers via 3D simulation Investigating the effects of radial fins on the PCM melting in horizontal systems Employing the arc radial fins instead of full circle fins to expedite the melting Achieving the fastest melting process via non-uniform distribution of the arc fins Utilizing combined radial-axial fin configurations to accelerate the phase-change